Determinación de adenovirus en niños menores de 5 años, con enfermedad diarreica aguda que asisten al Laboratorio Clínico del Hospital Básico de Yantzaza - Gordillo Cuenca, Dennis Xavier (2018)
Diarrheal disease is a health problem in both developed and underdeveloped countries. It is an important cause of morbidity and mortality in the population of children under 5 years old, achieving high levels of prevalence in communities with inadequate environmental hygiene, preservation of food, poor nutritional habits, limited access to health services and scarce economic development. Adenovirus infections cause a varied clinical spectrum, with a range that includes from the asymptomatic infection to disseminated disease with life threatening. So the objective of this work was to determine adenovirus in diarrheal stools of children under 5 years old that attend the clinical laboratory of the basic hospital of Yantzaza. The research method was descriptive and cross-sectional; for the analyzes of the samples the Adenovirus rapid cassette test was used, which is an immunocromatographic test for the rapid and qualitative identification of Adenovirus in stool samples. A total of 62 samples that correspond to the patient’s children less than 5 years of age who met the inclusion criteria were investigated, and the following conclusion was reached: Applying the immunochromatographic method to determine the adenovirus as a causal factor of childhood diarrhea, no positive case was found; what infers, that the diarrhea that the study patients presented was not caused by this virus. Keywords: Acute diarrheal disease, Adenovirus, children under 5 years old, immunochromatographic test.